A rare epithelioid leiomyoma of the vagina with sections of myxoid degeneration (Indian Journal of Case Reports, 2019)
Leiomyomas are common benign tumors in the uterus. Leiomyomas of the vagina are rare, and the epithelioid leiomyoma of the vagina is an extremely rare benign tumor. They are often accompanied by different symptoms. Here, I present the case of a 42-yearold woman, with local discomfort and dysuria. Enucleation of the tumor through a vaginal approach was done successfully without urethra injury as a healing method.